Taking Sides or Saving Lives: Existential Choices for the Humanitarian Enterprise in Iraq: Humanitarian Agenda 2015: Iraq Country Study - Hansen, Greg (Tufts Archival Research Center, 2008)
Paper dated June, 2007. Iraq places the frailties and fault-lines of the humanitarian enterprise in stark relief. Perhaps more than any other highly politicized context, Iraq has fuelled a defensiveness and sense of existential threat among many in the humanitarian profession. And yet, while Iraqis have paid long and dearly for the flaws in the international humanitarian apparatus, evidence from ground-level suggests that pronouncements of the demise of principled humanitarian action are premature. Iraq may provide the strongest affirmation yet of the endurance of the Dunantist ethos and of the principled practice of humanitarianism.